Enhanced microwave absorption properties of samarium-doped BiFeO3 Composites: Structural and electromagnetic analysis - Siti Nor Ain, Rusly; Arlina, Ali; Norliza, Ismail; Khamirul Amin, Matori; Ismayadi, Ismail; Idza Riati, Ibrahim (Elsevier Ltd., 2025)
The increasing use of electromagnetic (EM) technologies has raised concerns about electromagnetic interference (EMI), which can affect electronic systems and human health. Bismuth ferrite, BiFeO3 (BFO), is a promising material for microwave absorption due to its multiferroic properties, but it faces several limitations that affect its performance. This study aims to enhance the microwave absorption efficiency of BFO composite by modifying its structure and electromagnetic properties through samarium (Sm) doping. The undoped BFO and Sm-doped BFO samples were prepared using solid-state reactions and then incorporated into an epoxy resin polymer matrix with a ratio of 70:30 wt% to create a composite. The magnetic and dielectric testing demonstrated enhanced magnetization and improved dielectric properties, which significantly contributed to better impedance matching and a higher attenuation constant, leading to greater microwave absorption efficiency. Microwave absorption tests conducted in the 8–18 GHz range demonstrated significant improvements for Sm-doped BFO composites compared to the undoped BFO sample. Notably, the Sm-doped BFO sample with 0.2 Sm concentration and a thickness of 2 mm achieved a significant reflection loss (RL) of − 22.3 dB at 12.8 GHz. It also had a broader effective bandwidth compared to undoped BFO, showing improved microwave absorption due to samarium doping. These results demonstrate that Sm-doped BFO can improve the limitations of current MAMs by offering better absorption, broader bandwidth with a single layer and optimal thickness.